2005
DOI: 10.1258/0049475054037147
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of malignant diseases at the University of Benin Teaching Hospital

Abstract: This study was designed to evaluate the pattern of malignant diseases seen at the University of Benin Teaching Hospital over a 20-year period (January 1980-December 1999). A total of 2258 histologically confirmed malignant diseases were seen with the predominant tumours comprising carcinoma of the cervix (20.59%), breast (18.25%), prostate (7.13%), endometrium (6.47%) and colon and rectum (5.71%). We believe that the figure reported here represents an underestimate of the frequency of malignant tumours seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…4 In Benin, Okobia and Aligbe reported similar trend with gastrointestinal malignancies accounting for 12.9% of all malignant diseases. 5 This is in contrast to the finding of Abdul Aziz et al in which GIT cancers represented 29.3% of the total cancer burden in Saudi Arabia. 6 Colorectal carcinoma is the commonest malignancy of the gastrointestinal tract in Nigeria and it occurs more in the young and middle aged; adenocarcinoma being the predominant type.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…4 In Benin, Okobia and Aligbe reported similar trend with gastrointestinal malignancies accounting for 12.9% of all malignant diseases. 5 This is in contrast to the finding of Abdul Aziz et al in which GIT cancers represented 29.3% of the total cancer burden in Saudi Arabia. 6 Colorectal carcinoma is the commonest malignancy of the gastrointestinal tract in Nigeria and it occurs more in the young and middle aged; adenocarcinoma being the predominant type.…”
Section: Introductionmentioning
confidence: 58%
“…This concurs with most previous studies which show that colorectal cancer is the most common GIT cancer with figures ranging between 53-67%. 5,15,16 In developed countries, it ranks among the three most common cancers. 17 Earlier studies from Ibadan, Southern West Nigeria had showed lower incidence but after 2 decades, Iliyasu et al recorded 81% increase in colonic cancer from the same centre.…”
Section: Discussionmentioning
confidence: 99%
“…7 The percentage of benign cases in our series is lower than 72.6%, 90%, 71.3% and 73% reported respectively in Eku, and Zaria. [8][9][10] Other researchers like Mayun, Khan, Pradhan, Siddique etc have noted fibroadenoma to be the most common cause of breast lump followed by fibrocystic disease, than breast cancer or breast cancer than fibrocystic disease. [11][12][13][14] The age range of patients with breast lump in our study was 15-70 years.…”
Section: Discussionmentioning
confidence: 99%
“…A rising incidence of colorectal cancer has been reported from many regoins which were considered previously as an area of low incidence CRC [9][10][11]12] . This increase in the incidence of colorectal cancer has been attributed to improved awareness about cancer and a shift towards a western diet.…”
Section: Discussionmentioning
confidence: 99%